Determining critical factors of e-government adoption among accountants in Iraq - Bahjat, Sura Naufel (2018)
There are limited studies on e-government adoption among accountants in countries experiencing conflicts. Similarly, there are limited studies that aim to investigate the inefficient e-government adoption due to the lack of regulations support and poor information system. Hence, the objectives of this study were to investigate the factors influencing e-government adoption and whether regulation support plays a moderating role in Iraq. This study used the Unified Theory of Acceptance and Use of Technology (UTAUT) Model to develop the research framework. This study was underpinned by five variables representing (public performance expectancy, public facilitating condition, public effort expectancy, information system quality, and social influence) were tested, and regulation support was included as a moderator with five moderating hypotheses. Data were collected through OneDrive online survey compromising 400 sample, 108 from the Kurdistan Region, and 292 from Iraq. The result reveals that four variables (public performance expectancy, public facilitating condition, information system quality, and social influence) have a significant relationship with e-government adoption. However, public effort expectancy shows an insignificant relationship with e-government adoption. Interestingly, regulation support moderates the relationship between (public effort expectancy, information system quality, and social influence) and the e-government adoption. This study contributes to the richness of UTAUT model with the inclusion of information system quality and regulation support to the research framework. Also, this study offers valuable insights to the government and policy-makers who are responsible for assisting in the e-government service operations. The result also contributes to the explanation of e-government adoption levels and the government could formulate strategies to encourage employees to adopt e-government in the developing and conflict areas. Conclusions, limitations and suggestions for future studies are also highlighted.